Pengakuan dan Implementasinya terhadap Masyarakat Adat Moronene Hukaea Laea di Kabupaten Bombana - Faharudin Faharudin; Wa Ode Zamrud; Bakri Sulaeman (Wajah Hukum, 2023)
Recognition and Implementation of the Moronene Hukaea Laea Indigenous People in Bombana District. This study aims to explore the legal dimensions of Recognition of the Moronene Hukaea Laea Indigenous People in Bombana District, and to find out and understand how this recognition is implemented. This research is Empirical Legal Research, and was conducted in Bombana District, Southeast Sulawesi Province. Methods of data collection using interview techniques and field observations. All data, both Primary Data and Secondary Data, were analyzed using qualitative analysis techniques. The results of this study indicate that (1) Recognition of the Moronene Hukaea Laea Indigenous People in Bombana Regency based on laws and regulations has been carried out by the Regional Government in the form of Regional Regulations, (2) In its implementation, this Recognition has not been able to guarantee legal certainty regarding Community Rights Hukaea Laea custom. There are many weaknesses in the Regional Regulation in recognizing the Existence of the Hukaea Laea Indigenous People, which results in the implementation of this recognition not being effective.